Histomorphology of immunomodulation and PD1 expression in breast cancer tumor draining lymph nodes: Determinants of Breast Cancer Screening - Nayek, Suma; Sau, Sourav; Majumdar, Kaushik; Basu, Anupam; Bandyopadhyay, Arghya (Archives of Breast Cancer, 2022)
Background: Metastasis in tumor draining lymph nodes (TDLNs) is correlated with poor prognosis in breast cancers. It is associated with local immune suppression, which can be partly due to the higher expression of check point inhibitors in immune cells. The morphological manifestation of the underlying immunomodulation of TDLNs has been less investigated. Here, we present the histomorphological changes and PD1 expression pattern in metastatic and non-metastatic TDLNs in breast cancer patients. Methods: A total of 248 metastatic or non-metastatic TDLNs from 50 breast carcinoma samples were examined histologically and for PD1 expression in the present study. We assessed the immune response in these TDLNs as per histomorphological patterns on H&E stained slides, categorizing them into lymphocyte predominance, germinal center predominance and an un-stimulated pattern. Anti-PD1 immunohistochemistry was performed on all lymph nodes. The results were analyzed using SPSS version 23 and P value <0.05 was considered to be significant. Results: The lymph node metastasis in breast carcinoma was significantly higher at younger age, patients with higher tumor grade and lympho-vascular invasion in the primary tumor. The metastatic lymph nodes showed significantly higher densities of germinal centers with abnormal shapes, as compared to non-metastatic ones. There was significantly higher expression of PD1 in the immune cells of metastatic TDLNs. Conclusion: The identification of PD1 immunohistochemical profile along with histological changes of TDLNs should therefore be considered as a possible prognostic and predictive marker for lymph node metastasis. The patients with higher densities of germinal center with abnormal shape and increased PD1 expression should benefit from immune-check point inhibitor therapy.